A practical outcome scale for paediatric head injury. Issue 2 (1st February 2001) - Crouchman, M; Rossiter, L; Colaco, T; Forsyth, R
Abstract : Traumatic brain injury (TBI) is the commonest cause of acquired disability in childhood. A major obstacle to the evaluation of acute and rehabilitative therapies after TBI is the lack of simple descriptors of outcome. We developed the King's Outcome Scale for Childhood Head Injury (KOSCHI), as a specific paediatric adaptation of the original adult Glasgow Outcome Scale (GOS). The KOSCHI expands the five category GOS to provide increased sensitivity at the milder end of the disability range. The GOS category of "persistent vegetative state" was replaced by "vegetative". "Good recovery" was allocated two categories, in acknowledgement of the long term importance of relatively minor sequelae in a developing child. The scale was quick and easy to use. Inter-rater reliability studies show that even with such an apparently simple scale, some training may be required. The KOSCHI provides a practical scale for paediatric head injury which will enable clinicians to describe rate and extent of recovery, and evaluate the effects of service and research interventions.